2014
DOI: 10.1128/aac.01826-13
|View full text |Cite
|
Sign up to set email alerts
|

Statins Increase Rifampin Mycobactericidal Effect

Abstract: Mycobacterium leprae and Mycobacterium tuberculosis antimicrobial resistance has been followed with great concern during the last years, while the need for new drugs able to control leprosy and tuberculosis, mainly due to extensively drug-resistant tuberculosis (XDR-TB), is pressing. Our group recently showed that M. leprae is able to induce lipid body biogenesis and cholesterol accumulation in macrophages and Schwann cells, facilitating its viability and replication. Considering these previous results, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 41 publications
2
85
0
2
Order By: Relevance
“…The study further demonstrated that the simvastatinmediated decrease in bacterial growth was reversed by the presence of mevalonate, the product of HMG-CoA reductase, and suggested that statins control infection by phagolysosomal arrest of M. tuberculosis. These results were corroborated by those from a study by Lobato et al in which they showed that atorvastatin and simvastatin (2 M) significantly inhibited M. tuberculosis growth (circa 60% reduction) in macrophages and that this was again reversed by the presence of mevalonate (54). A previous study by Parihar et al also demonstrated that simvastatin treatment (20.6 mg/liter) could significantly reduce, by up to 4-fold (P Ͻ 0.001), the ability of the foodborne pathogen Listeria monocytogenes to grow inside mouse and primary macrophages, in a cholesteroldependent manner, and could significantly reduce bacterial burden and dissemination (by 100-fold) to the liver (P Ͻ 0.001) and spleen (P Ͻ 0.05) in infected mice (61).…”
Section: Effects Of Statins On Intracellular Growth Of Bacteriasupporting
confidence: 81%
See 3 more Smart Citations
“…The study further demonstrated that the simvastatinmediated decrease in bacterial growth was reversed by the presence of mevalonate, the product of HMG-CoA reductase, and suggested that statins control infection by phagolysosomal arrest of M. tuberculosis. These results were corroborated by those from a study by Lobato et al in which they showed that atorvastatin and simvastatin (2 M) significantly inhibited M. tuberculosis growth (circa 60% reduction) in macrophages and that this was again reversed by the presence of mevalonate (54). A previous study by Parihar et al also demonstrated that simvastatin treatment (20.6 mg/liter) could significantly reduce, by up to 4-fold (P Ͻ 0.001), the ability of the foodborne pathogen Listeria monocytogenes to grow inside mouse and primary macrophages, in a cholesteroldependent manner, and could significantly reduce bacterial burden and dissemination (by 100-fold) to the liver (P Ͻ 0.001) and spleen (P Ͻ 0.05) in infected mice (61).…”
Section: Effects Of Statins On Intracellular Growth Of Bacteriasupporting
confidence: 81%
“…A significant synergistic effect resulting in increased bacterial lysis has been reported with sublethal doses of penicillin and simvastatin (7.8 mg/liter) against pneumococcal growth in vitro (43), while atorvastatin and simvastatin (0.2 M) treatment increased the efficacy of rifampin against M. tuberculosis and M. leprae infection in vitro by approximately 50% (54). In addition, in vivo mouse studies showed that atorvastatin (80 mg/kg/day) treatment increased the efficacy of rifampin against M. leprae infection (P Ͻ 0.05) (54) and that simvastatin (25 mg/kg) treatment increased the in vivo activity of first-line anti-TB antibiotics, reducing the lung bacillary burden by Ͼ1 log 10 (P Ͻ 0.01) (82). Thangamani and colleagues demonstrated a positive synergistic effect of simvastatin on the antimicrobial effect of four topical antibiotics, mupirocin, fusidic acid, retapamulin, and daptomycin, against clinical isolates of multidrug-resistant S. aureus.…”
Section: Coprescription Of Statins With Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In TB mice models, treatment with statins significantly reduced the bacterial load and the pulmonary pathological effects of TB infection (Parihar et al, 2014). It was further shown in TB-infected macrophages and in mice models that treatment with statins improves the efficacy of first-line TB drug regimens and of rifampicin alone (Lobato et al, 2014;Skerry et al, 2014). It was demonstrated that statins improve bacterial clearance by the host and improve the efficacy of TB drugs by promoting autophagy through inhibition of the HMG-CoA reductase pathway (Parihar et al, 2014).…”
Section: Arg677trp (C2029t)mentioning
confidence: 95%